High performance of point-of-care rapid tests for advanced HIV disease diagnosis by lay providers in Malawi: Results from a prospective diagnostic accuracy study supporting decentralized advanced HIV disease screening - Agness Thawani; Ethel Rambiki; Jacqueline Huwa; Layout Gabriel; Aubrey Kudzala; Christine Kiruthu-Kamamia; Pachawo Bisani; Shameem Buleya; Nathan P. Ford; Cheryl C. Johnson; Ajay Rangaraj; Robert Luo; et al. (PLoS ONE, 2026)
CD4 testing is essential for identifying people with advanced HIV(AHD) disease and enabling delivery of the recommended diagnostic package including serum cryptococcal antigen (CrAG)and urine lipoarabinomannan(LAM) testing and prophylaxis. Suboptimal access to CD4 testing remains a major barrier to the scale-up of advanced HIV disease services, and there is limited evidence to inform strategies for improving access within constrained health systems. Although task-sharing for advanced HIV disease is being promoted, evidence on the performance of these diagnostics when delivered by lay providers in routine program settings remains limited. Lay providers (HIV diagnostic assistants) might be able to perform CD4 testing, serum cryptococcal antigen (CrAg) and urine lipoarabinomannan (LAM) tests using lateral flow assays (LFAs). We conducted a prospective diagnostic accuracy study comparing VISITECT® CD4 lateral flow assay results performed by HDAs and laboratory technicians, using paired quantitative PIMA CD4 results performed by nurses as the reference standard. We also compared serum cryptococcal antigen and urine lipoarabinomannan test results performed by HDAs and nurses. Implementation costs were estimated to assess the potential efficiency of task-sharing. We recruited 308 participants, the median CD4 was 248 cells/mm 3 ; and 115 participants (37.3%) had values below 200 cells/mm 3 . Sensitivity and specificity for determining CD4 below 200 cells/mm 3 using the VISITECT® CD4 LFA operated by HDAs were 94.8% (95% CI: 89.1–97.6%) and 92.2% (95% CI: 87.6–95.2%), respectively. HDAs achieved higher sensitivity and specificity than laboratory technicians. Subsequent serum-CrAg and urine-LAM test performed by HDAs and nurses showed an agreement of 98.1% (κ = 0.74) and 98.1% (k = 0.85), respectively. Incremental cost per CD4 test was US$8.69 when performed using the PIMA® CD4 quantitative device by a nurse and US$5.24 when performed using the VISITECT® CD4 semi-quantitative lateral flow assay by HDAs (2024 US dollars). Trained lay providers can accurately perform CD4, urine TB-LAM, and serum cryptococcal antigen testing. Our findings support task-sharing for decentralized advanced HIV disease testing; CD4 lateral flow assay testing is particularly suitable for peripheral health facilities that rely on lay providers and lack reliable electricity and laboratory infrastructure. This approach could play a critical role in expanding access to advanced HIV disease services.